The Implementation of Solar Panel with CCTV Camera in the National Road of Zambales, Philippines: A Proposal Study - Dr. Froilan D. Mobo (Genius Publishing Group, 2021)
The Province of Zambales is a peaceful place where you want to consider as a retirement place because of the beautiful nature site seeing. But there is particular problems that majority of the municipality in the province of Zambales, Philippines particularly in the towns of Subic and Castillejos cannot solve and there is a big problem that we are facing at night which is there are no street lights and CCTV Camera that can monitor the activity of the road during at night and in the morning because accidents are prone in the busy road during at night. There are so many violators in the National Road specially in rush hours, they do not follow the stipulated law related to National Road. Even enforcers don’t implement the said policy and guidelines because they don’t care about the possible impact and danger on the road. It’s been 2 years from now, since we experienced this kind of situation, even there is a law constituting the implementation of road courtesy under the Department of International and Local Government (DILG) Memorandum Circular No 2020-036 concerning the STRICT BAN OF TRICYCLES AND PEDICADS ALONG ALL NATIONAL HIGHWAYS to prevent from accidents. Now since most of the enforcer cannot monitor the national road event there is signage, the researcher is proposing to develop and come-up with a system that can be powered by a solar panel and can generate electricity to run the CCTV Camera and Street lights. İn this way it can help our enforcer to monitor the traffic within the National Road of Zambales and this can also save electricity and to prevent from any accidents that may occur and can send real-time report to the concerned offices. İn conclusion, the implementation of this kind of system is a big help to our government and to our constituent and drivers
Keywords: CCTV; Solar Panel; Camera; nature